2020
DOI: 10.1007/s12633-020-00630-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SiC and Al2O3 Reinforcement of Varied Volume Fractions on Mechanical and Micro Structure Properties of Interlock FSW Dissimilar Joints AA7075-T6-AA7475-T7

Abstract: In this research work, the effect of SiC and Al 2 O 3 reinforcements is analyzed on the interlock dissimilar joints. The joints are welded with different wt% of SiC and Al 2 O 3 (1 to 5 wt%) placed in the groove of 0.5 mm depth between the sheets. The rotational speed of 1400 rpm, weld speed of 30 mm/s and plunge speed rate of 0.06 mm/s are selected input parameters to perform the weld. Thereafter Micro-hardness, tensile strength and microstructure properties of interlock lap joints were investigated. AA7075 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…27 At various TRS, WS and PSR, the microstructure of joints on either advancing side and retreating side depicts fine, coarser, straight and elongated grains, which occurs mainly because of the related stress occurrence at high speeds and forward transverse tool operation. 28 Therefore, the TMAZ of joint with 1000 r/min of TRS with 0.30 mm/s WS, PSR of 0.06 mm/s and TRS of 1200 r/min, WS 30 mm/s, plunge feed rate 0.06 mm/s encapsulates both forms of grains in the weld regions. 29 From the microstructure observation, joint fabricated with 1400 r/min of TRS with 0.36 mm/s WS and PSR of 0.06 mm/s offers smoother diffusion at TMAZ/SZ interface on both the advancing and retreating sides.…”
Section: Microstructure Analysismentioning
confidence: 97%
“…27 At various TRS, WS and PSR, the microstructure of joints on either advancing side and retreating side depicts fine, coarser, straight and elongated grains, which occurs mainly because of the related stress occurrence at high speeds and forward transverse tool operation. 28 Therefore, the TMAZ of joint with 1000 r/min of TRS with 0.30 mm/s WS, PSR of 0.06 mm/s and TRS of 1200 r/min, WS 30 mm/s, plunge feed rate 0.06 mm/s encapsulates both forms of grains in the weld regions. 29 From the microstructure observation, joint fabricated with 1400 r/min of TRS with 0.36 mm/s WS and PSR of 0.06 mm/s offers smoother diffusion at TMAZ/SZ interface on both the advancing and retreating sides.…”
Section: Microstructure Analysismentioning
confidence: 97%
“…Increasing grain boundaries slows down the dislocation movement, strengthening the welded region. Anand and Sridhar 43 studied the effect of SiC and Al 2 O 3 reinforcement on various volume fractions in dissimilar FSW of AA7075 and AA7475 aluminum alloys. The authors compared the YS and UTS between SiC and Al 2 O 3 for the same weight% and found increased values in SiC-reinforced specimens.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It can be attributed to higher heat produced during the process, resulting in a brittle weld region that leads to shrinkage. 43 The factors that influence grain size in the NZ are (i) DRX which increases the dislocation density by preventing grain boundary slipping, thereby reducing the grain size and (ii) the annealing effect due to excessive peak temperature that increases grain size. 56,114 In addition, DRX includes mechanisms like dynamic recovery, continuous DRX (CRDX), discontinuous DRX (DDRX), and geometric DRX (GDRX).…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Recrystallized grains appear in the stir zone (SZ). Plastically deformed grains appear in thermomechanically affected zone (TMAZ) [8]. Die Region SZ, in which dynamic recrystallization produced by the stirring action of the tool results in refined grains, is subjected to high deformation and high heat input.…”
Section: Introductionmentioning
confidence: 99%